The Correlation Between Sleep Quality and Attention as Measured by Trail-Making Tests in Medical Faculty Students - Aldin, Muhammad; Nurhidayati, Ida Ratna; Maulana, Aya Yahya (Junior Medical Journal, 2023)
Introduction: Sleep quality is the ability of an individual to stay asleep and to get the right amount of Rapid eye movement (REM) and Nonrapid eye movement (NREM) sleep. Sleep quality is said to be good if a person gets enough sleep and does not get sleep disturbances. Sleep quality will affect a person's alertness, mood, concentration, and attention. Medical students in Indonesia have poor sleep quality; as many as 53% of students experience sleep disorders. This study aims to determine the relationship between sleep quality and attention in medical students at Yarsi University. Methods: This study is a quantitative study with a cross-sectional design. This type of research is analytically observational. The number of samples of this study was 31 respondents who were active students of the Faculty of Medicine, YARSI University, in 2019. The research instrument used to measure sleep quality is the Pittsburgh Sleep Quality Index (PSQI) and the trailmaking test (TMT) for attentional testing. The data analysis method used univariate and bivariate analysis with the Chi-square statistical test. Result: Twenty-one people had poor sleep quality. Among respondents with poor sleep quality, 12 respondents (57.1%) had poor attention, and nine respondents (42.9%) had good attention. Conclusion: Sleep quality and attention have no significant relationship with a p-value> 0.05. In the view of Islam, it follows the sleep pattern recommended by the Prophet Muhammad. Good sleep quality will improve quality of life.